Kinetics of cluster growth in expanding rare-gas jet - Ratner, M. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The growth of clusters in an overcooled atomic jet is calculated with the simultaneous allowance for two processes: the condensation of supersaturated gas and the cluster-cluster aggregation. These processes are consistently described within a quasi-equilibrium approach for large enough clusters, while their nucleation stage is allowed for phenomenologically by the use of a fitting parameter. The theory quantitatively describes the experimental dependence of the mean cluster size on the initial gas temperature within a broad range of sizes. The mean size of clusters, their distribution over sizes and the contribution of clusters to the total mass of the jet are calculated versus the distance from the gas ejection point (nozzle entry). It is shown that these characteristics are mainly determined by the initial gas entropy which is equivalent to the empirical law of corresponding jets. The size distribution function has a halfwidth exceeding the mean cluster size and is close (on a relative scale) to an universal curve. The broad size distribution of clusters should be taken into account when analyzing spectroscopic data on the size dependence of electronic processes in a cluster.